Determinants of patients' satisfaction and trust toward healthcare service environment in general practice clinics - Ai, Yun; Rahman, Muhammad Khalilur; Newaz, Md. Shah; Gazi, Md. Abu Issa; Rahaman, Md. Atikur; Mamun, Abdullah Al; Chen, Xia (Frontiers in Psychology, 2022)
This study aimed to examine the healthcare service environment, patients' experience, and responses toward healthcare services in private general practice (GP) clinics. Self-administered questionnaires were used for collecting data from 367 respondents with prior experience in visiting the general practice clinics in Malaysia. SmartPLS statistical tool was used to test the underlying hypotheses. The results revealed that ambiance, service delivery, interior decor, and cleanliness had a significant influence on patients' trust and satisfaction while the exterior design is neither associated with satisfaction nor trust. Patients' satisfaction and trust had a higher significant effect on their repatronage intention, willingness to pay for a premium healthcare service, and engagement in word-of-mouth for healthcare services. In practice, both the service delivery and ambiance features of the healthcare services environment might be optimized by GP clinics. This research provides significant insights from the patients' perspective toward the GP clinics' healthcare services environment.